Using DArT Markers to Monitor Genetic Diversity throughout Selection: A Case Study in Nebraska's Winter Wheat Breeding Nurseries. Issue 6 (1st November 2013) - El‐basyoni, Ibrahim; Baenziger, P. Stephen; Dweikat, Ismail; Wang, Dong; Eskridge, Kent; Saadalla, Mohamed
ABSTRACT: Assessing the genetic relationship among wheat ( Triticum aestivum L.) lines in the intermediate generations of a breeding program has important consequences on conserving genetic variability for selection in later generations. The objectives of this study were to (i) determine the breadth of the genetic base of two F3:6 nurseries and (ii) to monitor the effect of selection on the genetic diversity. Two independent F3:6 nurseries (2010 and 2011 seasons) were used; the first nursery contained 276 lines and two local check cultivars genotyped using 1925 polymorphic diversity array technology (DArT) markers while the second nursery contained 278 lines plus the same local check cultivars genotyped using 2236 polymorphic DArT markers. The F3:6 nurseries, 2010 and 2011, were each grouped into three main clusters. Overall, the results suggested that, in both years, the difference among clusters was significant, and the genetic diversity in the F3:6 nurseries exceeded that between the two check cultivars. The results for the two nurseries showed that each cluster in the F3:6 nurseries was represented in the F3:7 and F3:8 with at least one line, except for one cluster in the 2011 nursery which was not represented in F3:8 . We concluded that much of the genetic diversity was maintained while advancing lines from F3:6 to F3:7 ; however, as the selection intensity increases, for example from F3:7 to F3:8, the effect of selection and the importance of monitoring genetic diversity using DNA molecular markers increases.